Economic stress and child outcomes: the family stress model among Asian American families during COVID-19 - Fanta, Annie; Kim, Sei Eun; Huang, Cindy J.; Tsai, William; Huang, Cindy Y. (Frontiers in Psychology, 2025)
Limited research has examined the impact of financial stress on families since the onset of COVID-19, specifically among Asian American (AA) parents. Informed by the Family Stress Model, this study examined the short-term longitudinal links between economic stress, parental psychological distress (i.e., anxiety and depression symptoms), positive parenting behaviors, and child outcomes three months later (i.e., child internalizing and externalizing problems). Results indicated that Time 1 (T1) parental economic stress was directly and positively associated with positive parenting behaviors at T1 and child internalizing problems at Time 2 (T2). Parental psychological distress at T1 was directly and negatively associated with positive parenting behaviors at T1. Positive parenting behaviors at T1 were directly and negatively associated with child externalizing problems at T2. Parental economic stress at T1 had an indirect effect on child externalizing problems at T2 through parenting behaviors. These findings highlight the need for clinical interventions targeted at improving parent mental health and promoting positive parenting behaviors during times of economic hardship to prevent adverse child outcomes. Furthermore, policy efforts aimed at alleviating economic stress among at-risk families can help reduce social inequality and buffer the harmful effects of economic stress on AA parents and families.